The nation-state in a globalising media environment - Chin, Yik-Chan (Javnost (Ljubljana), 2003)
Since the late 1990's, China's television industry has undergone a major re-organisation. This was particularly evident after China's accession to the WTO in December 2001. One of the central issues facing China's broadcasting is the establishment of sound guiding principles for state regulation. The purpose of this paper is to analyse China's regulatory policies of transborder television drama flow. Through this, I engage in the debate over the role of the state in a globalising media environment. I will demonstrate that, though the transborder media poses a challenge to a national media system and culture, the local state still plays a crucial role in regulating domestic cultural policies and guiding development. The paper begins by reviewing the existing debates on the communication sovereignty of nation-state with particular focus on broadcasting. It is followed by a brief introduction to the changing environment of China's television industry. This is aimed at providing a context for the analysis and at articulating the debates with the empirical phenomena. The rest of the paper covers two parts. The first part sketches the structure of the broadcasting regulatory system in China, and the development of its television drama in the late 1980's and the earlier 1990's. The second one deals with the recent changes of the Chinese regulations on governing the transborder television drama flow and investment
Keywords: Kitajska; radio; množični mediji; mass media; television; televizija; state; država; regulacija; nadzor; demokratizacija; medijska politika; globalizacija; globalization